Monetary Circulation in Armenia in the Hellenistic and Parthian-Roman Periods (Some Remarks) - Mousheghian, Anahit (Anabasis. Studia Classica et Orientalia, 2019)
Numismatic evidence sheds a great deal of information about the history of Armenia in Antiquity. The earliest numismatic coin finds in Armenia date to the fifth century B.C. unearthed at the fortress of Erebouni. Four basic monetary groups were in circulation in Armenia until the end of first century B.C.: Seleucid, Parthian, Roman and Armenian. When Armenia entered the Hellenistic world in the fourth century B.C., the country was introduced to the Attic monetary weight standard that in time became the standard used in Asia. Armenia was a buffer state between East and West. Coins circulated in Armenia for political and economic reasons owing to the country’s favorable geographical location. The coins of the latter Artaxiads are classified as Armeno-Roman. The wide circulation of Roman Imperial denarii of the first-second century A.D. in Armenian markets coincided with the rule of the early Armenian Arsacid dynasty.